Services provided by browsing centres with reference to Udumalpet taluk from client’s perspective - Tamilselvi, S.; Karpagavalli, V.; Karthika, B. (Indian Journal of Computer Science, 2017)
The rapid progress made in the field of information technology has revolutionized the world of communications. The world is gradually becoming a global village as interaction among people all over the world has become more frequent than even before. Through internet people from all countries can now share information, ideas, stories, data, and opinions. An internet protocol telephony network needs to have the capability to deliver voice, video, or data on the same network with assured quality of services. The invention of the telegraph, telephone, radio, and computer set the stage for this unprecedented integration of capabilities. The internet is at once a world-wide broadcasting capability, a mechanism for information dissemination and a medium for collaboration and interaction between individuals and their computers irrespective of geographic location. Unlike other businesses, the business of browsing centre provides multivariate uses such as educational, informative, advisory, and entertainment to customers. Therefore, customer expectations will be more on browsing centre and they might expect the perfect and absolute services. Therefore, browsing centres have an obligation to provide better services not only to retain their customers but also to withstand the competitive market through their services and efficiency.